Textualización de la oralidad y tradiciones discursivas en los microrrelatos del Siglo de Oro - Cristina Tabernero Sala (Les Cahiers de Framespa)
This paper analyzes a large number of micro-stories of the sixteenth and seventeenth centuries, in order to conclude whether we can speak, at least from a linguistic point of view, of a discoursive tradition characterised by the integration of orality in writing. The result of the review of orality textualization in Golden Age micro-stories shows that these are conditioned by dialogue, in direct or indirect reproduction. The golden story does not follow, in short, a scheme of distinguishing linguistic features; they are in close dependence on the genre that accommodates them. Specifically, orality cannot be considered an identifying element, able to make story different from other traditions.